45.8k views
3 votes
If the sum of the zereos of the quadratic polynomial is 3x^2-(3k-2)x-(k-6) is equal to the product of the zereos, then find k?

User BlackEye
by
4.9k points

1 Answer

3 votes

Answer:

2

Explanation:

So I'm going to use vieta's formula.

Let u and v the zeros of the given quadratic in ax^2+bx+c form.

By vieta's formula:

1) u+v=-b/a

2) uv=c/a

We are also given not by the formula but by this problem:

3) u+v=uv

If we plug 1) and 2) into 3) we get:

-b/a=c/a

Multiply both sides by a:

-b=c

Here we have:

a=3

b=-(3k-2)

c=-(k-6)

So we are solving

-b=c for k:

3k-2=-(k-6)

Distribute:

3k-2=-k+6

Add k on both sides:

4k-2=6

Add 2 on both side:

4k=8

Divide both sides by 4:

k=2

Let's check:


3x^2-(3k-2)x-(k-6) \text{ with }k=2:


3x^2-(3\cdot 2-2)x-(2-6)


3x^2-4x+4

I'm going to solve
3x^2-4x+4=0 for x using the quadratic formula:


(-b\pm √(b^2-4ac))/(2a)


(4\pm √((-4)^2-4(3)(4)))/(2(3))


(4\pm √(16-16(3)))/(6)


(4\pm √(16)√(1-(3)))/(6)


(4\pm 4√(-2))/(6)


(2\pm 2√(-2))/(3)


(2\pm 2i√(2))/(3)

Let's see if uv=u+v holds.


uv=(2+2i√(2))/(3) \cdot (2-2i√(2))/(3)

Keep in mind you are multiplying conjugates:


uv=(1)/(9)(4-4i^2(2))


uv=(1)/(9)(4+4(2))


uv=(12)/(9)=(4)/(3)

Let's see what u+v is now:


u+v=(2+2i√(2))/(3)+(2-2i√(2))/(3)


u+v=(2)/(3)+(2)/(3)=(4)/(3)

We have confirmed uv=u+v for k=2.

User Nikola Dimitrovski
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.